Rheology of drag reducing agents on crude oil systems (2021)
Drag reduction is becoming one of the main points of interest for researchers attempting to increase transport efficiency for all kinds of fluids, with crude oil being one of the main goals due to its high viscosity and economic relevance. This study tries to establish a consistent methodology to evaluate drag reduction in rheometers, using heavy crude oil as the focus. Dilutions using xylene were performed to reduce the viscosity of the system allowing turbulence inside a Couette cell to be achieved. On the other hand, drag reduction results show a significant change in viscosity and torque profiles when polyisobutylene (PIB) with molecular weight of 10^6 g/mol is added in concentrations between 2000-30000 ppm to the oil samples. Whereas using carboxymethyl cellulose (CMC) with a molecular weight of 9000 g/mol as a water-soluble polymer at 1000 ppm makes tests non-replicable, due to the presence of two distinct phases inside the rheometer. Initial degradation studies were carried out, managing to reassure the capabilities of PIB to resist mechanical degradation, proving to be a suitable drag reducing agent with the preliminary rheometer tests performed. A reproducible methodology, to study oil soluble drag reducing agents and a normalization approach on how to treat rheometric data as a tool for the evaluation of the drag reduction phenomenon is presented.